2016
DOI: 10.1016/j.scitotenv.2016.06.188
|View full text |Cite
|
Sign up to set email alerts
|

Five primary sources of organic aerosols in the urban atmosphere of Belgrade (Serbia)

Abstract: Biomass burning and primary biological aerosol particles (PBAPs) represent important primary sources of organic compounds in the atmosphere. These particles and compounds are able to affect climate and human health. In the present work, using HPLC-orbitrapMS, we determined the atmospheric concentrations of molecular markers such as anhydrosugars and phenolic compounds that are specific for biomass burning, as well as the concentrations of sugars, alcohol sugars and D- and L-amino acids (D-AAs and L-AAs) for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 94 publications
(135 reference statements)
0
24
0
Order By: Relevance
“…Arabitol and mannitol concentrations observed in our study are similar to those found by Caumo et al (2016) for São Paulo in winter of 2012 and 2013, Gosselin et al (2016) in a semiarid montane environment and Burshtein et al (2011) in Israel (Table 1). However, higher concentrations were observed in numerous studies as presented in Table 1 (Bauer et al, 2008b;Graham et al, 2003;Urban et al, 2014;Zhang et al, 2010;Rathnayake et al, 2016;Zangrando et al, 2016;Gosselin et al, 2016 -rainy period). These locations are examples of sampling sites in urban and forest environments, rendering the differences in concentrations mostly due to the difference in land use characteristics and/or sampling period.…”
Section: Carbohydrate Concentrationsmentioning
confidence: 91%
See 2 more Smart Citations
“…Arabitol and mannitol concentrations observed in our study are similar to those found by Caumo et al (2016) for São Paulo in winter of 2012 and 2013, Gosselin et al (2016) in a semiarid montane environment and Burshtein et al (2011) in Israel (Table 1). However, higher concentrations were observed in numerous studies as presented in Table 1 (Bauer et al, 2008b;Graham et al, 2003;Urban et al, 2014;Zhang et al, 2010;Rathnayake et al, 2016;Zangrando et al, 2016;Gosselin et al, 2016 -rainy period). These locations are examples of sampling sites in urban and forest environments, rendering the differences in concentrations mostly due to the difference in land use characteristics and/or sampling period.…”
Section: Carbohydrate Concentrationsmentioning
confidence: 91%
“…These locations are examples of sampling sites in urban and forest environments, rendering the differences in concentrations mostly due to the difference in land use characteristics and/or sampling period. Higher concentrations are found in places that are less urbanised and with more biogenic sources, such as a tropical forest (Zhang et al, 2010), suburban area (Bauer et al, 2008b), agroindustrial area (Urban et al, 2014), rainforest (Graham et al, 2003), smaller cities Zangrando et al, 2016) and in more humid periods (Gosselin et al, 2016). Moreover, bioaerosol concentrations can vary depending on meteorological conditions (Emygdio et al, unpublished results).…”
Section: Carbohydrate Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3), it is likely that the observed FAAs originated from distant sources. However, FAAs and particularly glycine have been also associated with biomass burning emissions (Samy et al, 2013;Violaki and Mihalopoulos, 2010;Zangrando et al, 2016). In Finland wood burning, which is a typical type of domestic heating in winter, is the most presumable source of over one third of the PM 2.5 emissions (Laakso et al, 2003;Saarnio et al, 2012).…”
Section: Overview Of Meteorological Factors and Sourcesmentioning
confidence: 99%
“…According to EB ratios and the location, we can conclude that Sb comes from vehicular sources. [151,164,165] or industrial (e.g., mining ores, steel plant, cement plants) [149,166,167].…”
Section: Discussionmentioning
confidence: 99%